Does microscopic experience influence learning curve in endoscopic ear surgery? A multicentric study. Issue 1 (February 2021) - Lucidi, Daniela; Fernandez, Ignacio Javier; Botti, Cecilia; Amorosa, Luca; Alicandri-Ciufelli, Matteo; Villari, Domenico; Presutti, Livio
Abstract: Objective: The aim of the present study was to illustrate the learning curve of endoscopic type-1 tympanoplasty comparing experts in microscopic otology versus neophyte surgeons. Methods: Eight ear surgeons, from tertiary referral centers, who had performed at least 30 endoscopic type 1 tympanoplasties were included in the study. Demographic data and medical records regarding the first 30 endoscopic type-1 tympanoplasties were retrospectively collected by each surgeon. A 14-questions survey focused on subjective aspects of the learning curve was administered. Surgeons were divided in two groups: one with previous experience in microscopic ear surgery (group 1) and one with no previous experience in ear surgery (group 2). The learning curve of endoscopic type 1 tympanoplasty was compared between the groups. Results: Mean surgical time was 89.2 min in group 1 vs. 79.5 min in group 2 ( p  < 0.01). When divided in 5 surgeries-steps, the only significant difference was appreciated in the first 5 surgeries with a longer mean time in group 1 vs. group 2 (+28.4 min; p  < 0.05). Conclusions: Surgeon's previous experience may influence the EES learning curve. Our results show that the first 5 surgical procedures are more challenging for surgeons experienced in microscopic surgery, subsequently the curve progression improves sharply and appears reversing the initial trend by the end of the 30 surgeries.